Is It Possible to Intervene in the Capacity of Trypanosoma cruzi to Elicit and Evade the Complement System? - Ramírez-Toloza, Galia; Aguilar-Guzmán, Lorena; Valck, Carolina; Menon, Smrithi S.; Ferreira, Viviana P.; Ferreira, Arturo (Frontiers in Immunology, 2021)
Chagas’ disease is a zoonotic parasitic ailment now affecting more than 6 million people, mainly in Latin America. Its agent, the protozoan Trypanosoma cruzi, is primarily transmitted by endemic hematophagous triatomine insects. Transplacental transmission is also important and a main source for the emerging global expansion of this disease. In the host, the parasite undergoes intra (amastigotes) and extracellular infective (trypomastigotes) stages, both eliciting complex immune responses that, in about 70% of the cases, culminate in permanent immunity, concomitant with the asymptomatic presence of the parasite. The remaining 30% of those infected individuals will develop a syndrome, with variable pathological effects on the circulatory, nervous, and digestive systems. Herein, we review an important number of T. cruzi molecules, mainly located on its surface, that have been characterized as immunogenic and protective in various experimental setups. We also discuss a variety of parasite strategies to evade the complement system - mediated immune responses. Within this context, we also discuss the capacity of the T. cruzi infective trypomastigote to translocate the ER-resident chaperone calreticulin to its surface as a key evasive strategy. Herein, it is described that T. cruzi calreticulin inhibits the initial stages of activation of the host complement system, with obvious benefits for the parasite. Finally, we speculate on the possibility to experimentally intervene in the interaction of calreticulin and other T. cruzi molecules that interact with the complement system; thus resulting in significant inhibition of T. cruzi infectivity.